A methodological approach for designing and sequencing product families in Reconfigurable Disassembly Systems - Ignacio Eguia; Sebastián Lozano; Jesus Racero; Fernando Guerrero (Journal of Industrial Engineering and Management (JIEM), 2011)
Purpose: A Reconfigurable Disassembly System (RDS) represents a new paradigm of automated disassembly system that uses reconfigurable manufacturing technology for fast adaptation to changes in the quantity and mix of products to disassemble. This paper deals with a methodology for designing and sequencing product families in RDS. Design/methodology/approach: The methodology is developed in a two-phase approach, where products are first grouped into families and then families are sequenced through the RDS, computing the required machines and modules configuration for each family. Products are grouped into families based on their common features using a Hierarchical Clustering Algorithm. The optimal sequence of the product families is calculated using a Mixed-Integer Linear Programming model minimizing reconfigurability and operational costs. Findings: This paper is focused to enable reconfigurable manufacturing technologies to attain some degree of adaptability during disassembly automation design using modular machine tools. Research limitations/implications: The MILP model proposed for the second phase is similar to the well-known Travelling Salesman Problem (TSP) and therefore its complexity grows exponentially with the number of products to disassemble. In real-world problems, which a higher number of products, it may be advisable to solve the model approximately with heuristics. Practical implications: The importance of industrial recycling and remanufacturing is growing due to increasing environmental and economic pressures. Disassembly is an important part of remanufacturing systems for reuse and recycling purposes. Automatic disassembly techniques have a growing number of applications in the area of electronics, aerospace, construction and industrial equipment. In this paper, a design and scheduling approach is proposed to apply in this area.Originality/value: This paper presents a new concept called Reconfigurable Disassembly System, which represents disassembly systems with reusability, scalability, agility and reconfigurability features. These features and some specific costs are considered as part of the proposed methodology.
Keywords: 650; linear programming; sequencing; disassembly; reconfigurable manufacturing